Homeschooling parents in California: Attitudes, beliefs and behaviors associated with child's vaccination status. Issue 8 (18th February 2020) - Mohanty, Salini; Joyce, Caroline M.; Delamater, Paul L.; Klein, Nicola P.; Salmon, Daniel; Omer, Saad B.; Buttenheim, Alison M.
Abstract: Background: Senate Bill 277 (SB277) banned nonmedical exemptions from school-entry vaccination requirements for children attending classroom-based schools in California, but excluded homeschooled children from vaccination requirements. Thus, it was hypothesized that more parents would choose to homeschool to avoid vaccination requirements in response to SB277. There is limited literature on the vaccine attitudes, beliefs, and behaviors among the homeschooling population in the US, despite an overall increase in homeschooling nationwide and documented vaccine-preventable disease outbreaks within the homeschooled child population. Methods: Between November 2018 and January 2019, we conducted a cross-sectional online survey among homeschooling parents with at least one child in grades K-8 who is currently enrolled in one of the legally-acceptable mechanisms to homeschool in California: (1) home-based private school satellite program (PSP), or (2) public or charter independent study program (ISP) with no classroom-based instruction. Results: Among 140 homeschooling parents from 8 schools in California, 71% reported that their youngest child in grade K-8 was up-to-date on immunizations at kindergarten-entry and 56% reported that they made the decision to homeschool their child after the implementation of SB277. Compared to homeschooling parents whose child was up-to-date at kindergarten entry, homeschooling parents whose child was not up-to-date at kindergarten entry reported higher concerns over vaccine safety and effectiveness, more frequently cited immunization mandates as a reason to homeschool, and were more likely to report having considered moving out of California due to immunization mandates. Conclusion: There was variation in vaccine attitudes and beliefs within the homeschooling population in this sample. Immunization mandates were a factor in the decision to homeschool for some parents in this sample, supporting the hypothesis that vaccine-hesitant parents considered homeschooling as a way to avoid immunization mandates such as SB277. Future studies should explore the complexities around vaccine attitudes, beliefs and behaviors among homeschooling populations.